Pengaruh Pengawasan Terhadap Disiplin Kerja Pegawai Non PNS Pada Rumah Sakit Jiwa Tampan Provinsi Riau - Rofidah, Siti (Eko dan Bisnis: Riau Economic and Business Review, 2023)
This research was conducted at Taman Mental Hospital, Riau Province, which is located at Jl. HR. Soebrantas Km. 12.5 New Intersection, Handsome District, Pekanbaru City. Samples were taken as many as 64 people. Data analysis in this study used descriptive and quantitative analysis methods. Descriptive is comparing actual facts with theories related to the problem in order to draw a conclusion and tabulate it in the form of frequency distribution tables. While the quantitative research method is based on data that can be calculated to produce a solid assessment. The results of a simple linear regression study in this study were Y = 14.833 + 0.627 X. By using the t test, a ttable value of 1.998 was obtained and a tcount value of 6.313 means that tcount = 6.313> ttable = 1.998 which means that supervision influences work discipline in mental hospitals Riau Provincial Park with a large influence of 39.1%